Mechanical and morphological characteristic investigations of deinked used newsprint paper via ultra-sonochemistry method - SAHARMAN GEA; SRI RAHAYU; ANDRIAYANI ANDRIAYANI; AVERROES FAZLUR RAHMAN PILIANG; NONI OKTARI (Jurnal Natural, 2020)
Printed newspaper is one of the print-based media published daily in large quantities. The focus of this research is to remove the ink from used newsprint with alkaline treatment by using ultrasound sonochemistry method. Newsprint sheets collected were characterized by mechanical and morphology tests using FT-IR, XRD, tensile test and SEM. FT-IR spectra analysis shows the absorption of C=C functional groups as the main components of newspapers at 1427 and 1635 cm-1 wavelengths. The treatment with alkaline solution increased the mechanical strength properties of paper. SEM morphology analysis result shows that the surface of paper becomes more rough after ultrasound-alkaline treatment compared to paper without ultrasound treatment (conventional treatment). The crystallinity value decreased with alkaline treatment. The longer the ultrasound duration was, the lower the crystallinity degree became.